Lobola in Eswatini: Exploring Male Vulnerabilities through Kinship Making - Ngwenyama, Nosisa Nolwazi (Social Anthropology, 2023)
The costly performances and displays of emalobolo and marriage by emaSwati aged 25 years to 35 years, during a time where 47% of the youth in Eswatini is unemployed has increased over the last two decades, while the legal marriage rates have decreased in the same period. The ethnographic study conducted predominantly online, in the Kingdom of Eswatini over eight months, during the COVID-19 pandemic uses qualitative methods to investigate the relationship between marriage and lobola practice, the performances of masculinity and how these performances influence and shape kinship making and the creation of family. The processes and procedures ascribed to emalobolo and marriage are not necessarily followed by the participants, as they make decisions and take actions that give the best possible outcomes for those involved. Family and kin relations produced during emalobolo magnify the tensions between consanguineal relatives and often friends take on the responsibilities of family members thus becoming family. The process of lobola also reveals the performative nature of class and social mobility, and places pressure on men to provide even when they cannot. The financial pressures and expectations placed on men to provide financially for members of their families, expose vulnerabilities in men, in ways that hegemonic masculinity neglects and erases. The embodiment of kuhlonipha and how it is practised by men and women help them strive for happiness and do what is right in the contexts they encounter as they navigate emalobolo, marriage and the afterlife of it all. My analysis shows that the creation of new family and kinship bonds through kulobola and marriage and the financial implications of them, expose male vulnerabilities that exist among Swazi men.